Factor Xa inhibition mitigates tacrolimus-induced tubulointerstitial fibrosis via the PI3K/p-AKT pathway - Mohamed Sadek Abdel-Bakky, Noura Bader Alharbi (Journal of Applied Pharmaceutical Science, 2025)
Tacrolimus (TAC) is one of the effective immunosuppressant drugs frequently used in different organ transplantation to prevent allograft rejection. The use of TAC is associated with nephrotoxicity, especially tubulointerstitial fibrosis (TIF), a complication that limits its use. The coagulation system involvement in the development of TIF-resulted from TAC, is not known. Therefore, the aim of the current work is to explore the role of the coagulation system activation against TAC-induced TIF. Furthermore, the possible protective role of the indirect Factor Xa inhibitors, rivaroxaban (RIV), against TAC-inducing TIF is also investigated. Normal, RIV-treated, TAC-treated, and TAC+RIV-treated groups were used. Renal toxicity markers, blood parameters, histopathology changes, and renal expression of fibrinogen, p-AKT, PI3K, TGF-β, and fibronectin were assessed. RIV-treated mice displayed improvement in renal architecture, blood glucose level, and renal and blood parameters deteriorated by TAC treatment. Moreover, RIV decreased tubular and glomerular expression of fibrinogen, p-AKT, PI3K, TGF-β, and fibronectin, increased by TAC treatment. FX activation mediates TAC-induced TIF through PI3K/p-AKT pathway. Therefore, RIV may serve as an effective adjunctive therapy to mitigate the renal consequences of calcineurin inhibitor use.
Keywords: Tacrolimus, coagulation, p-AKT, PI3K, tubulointerstitial fibrosis, rivaroxaban